The Use of Interactive Learning Media of Educaplay Games in Increasing Students' Learning Motivation in Islamic Cultural History Subjects - Kamilatuzahra Kamilatuzahra; Siti Istiqomah (Ngaji: Jurnal Pendidikan Islam, 2025)
Abstract: This study aims to determine the implementation of the use of the educaplay game in increasing student learning motivation at MTs Jam'iyyatul Khair Ciputat. The method used in this study is qualitative with a field research approach. Data were collected through several techniques, namely observation, interviews, documentation, and questionnaire distribution. The subjects in this study included the principal, homeroom teacher, Islamic Cultural History teacher, and four students of class VIII A. The data analysis process was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of interactive learning media in the form of the educaplay game in the Islamic Cultural History (SKI) subject at MTs Jam'iyyatul Khair took place effectively. The implementation showed that the learning process with the help of the educaplay game ran smoothly, marked by the teacher's ability to convey the material clearly and excellent skills in operating the technology platform. Students also showed increased motivation in learning Islamic Cultural History, as seen from high curiosity, enthusiasm in completing assignments, discipline in submitting assignments on time, and the results of the students' grades in the Islamic Cultural History subject met the KKM standard.